Genome-based Study on the Mechanism of Rare Earth Neodymium Ions Increasing Ethanol Production from Clostridium thermocellum - Jinna Cui; Tiantian Sun; Lixia Liu; Zhanying Liu (BioResources)
The escalating global demand for energy, coupled with heightened environmental concerns, has rendered the identification of sustainable and environmentally friendly alternative energy sources imperative. Ethanol derived from cellulosic fibers is garnering significant interest as a clean and renewable energy source. Among the various production methods, consolidated bioprocessing (CBP) stands out due to its distinct advantages. Clostridium thermocellum is considered an exemplary candidate strain for the CBP production of cellulosic ethanol; however, the low yield of ethanol remains a critical limiting factor. In the preceding study, it was demonstrated that neodymium ions could enhance the ethanol production of C. thermocellum. In this study, the whole genome sequences of the original strain C. thermocellum ATCC 27405 (C0) and the strain with added neodymium ions (Nd3+) (C1) were sequenced and analyzed. The findings indicated that the increased expression of pyruvate-ferric redox protease (PFO) resulted from mutations in its promoter region. Furthermore, an analysis of the sequencing data, along with the results from single knockout experiments, revealed that mutations in the genes encoding methyl-accepting chemotaxis proteins (MCP) and type 3a cellulose-binding domain protein (Type) genes were correlated with enhanced ethanol production. This study serves as a reference for the targeted modification of C. thermocellum to optimize ethanol production.